Respuesta :

Answer:

infinitely many solutions

Step-by-step explanation:

solve  by substitution:

solve equation 1 for y: - y = 7 - 4x; divide by -1 to simplify into y = -7 + 4x

Substitute - 7 + 4x into the second equation to obtain:

3(-7 + 4x) - 12x = -21, which yields:

-21 + 12x - 12x = -21, which simplifies 0 = 0

a result of 0 = 0 means infinite solutions such as:

(2,1), (3, 5), (4, 9), (5, 13), (6, 17)....

Answer:

infinite soulutions

Step-by-step explanation:

i just did it and it was right on ed2021...